Trade in knowledge : intellectual property, trade and development in a transformed global economy / edited by Antony Taubman, Jayashree Watal. - Taubman, Antony; Watal, Jayashree (Cambridge University Press, 2022)
Technological change has transformed the ways knowledge is developed and shared internationally. Accordingly, in the quarter-century since the WTO was established, and since its Agreement on Trade-Related Aspects of Intellectual Property Rights came into force, both the knowledge dimension of trade and the functioning of the IP system have been radically transformed. The need to understand and respond to this change has placed knowledge at the centre of policy debates about economic and social development. Recognizing the need for modern analytical tools to support policymakers and analysts, this publication draws together contributions from a diverse range of scholars and analysts. Together, they offer a fresh understanding of what it means to trade in knowledge in today's technological and commercial environment. The publication offers insights into the prospects for knowledge-based development and ideas for updated systems of governance that promote the creation and sharing of the benefits of knowledge.